2013
DOI: 10.1111/1365-2435.12144
|View full text |Cite
|
Sign up to set email alerts
|

Under pressure: how a Mediterranean high‐mountain forb coordinates growth and hydraulic xylem anatomy in response to temperature and water constraints

Abstract: Summary1. Plant growth in Mediterranean high mountains is limited by the double climatic stress of low winter temperatures and summer drought. Elevational shifts in response to climate change may be complex for species whose distribution is constrained by several climatic factors. 2. We used herb-chronology, that is, the analysis of annual rings in the secondary root xylem of perennial forbs, to evaluate life-long factors constraining secondary growth and xylem hydraulic anatomy along an elevational gradient f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
37
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 76 publications
(141 reference statements)
6
37
0
2
Order By: Relevance
“…Stronger and more defined associations emerged when the climatic data were aligned according to the DD temperature thresholds at high elevation (especially for CD in the first ring sectors; Figs 6 and 7), but not at lower elevations (see Cuny et al, 2015). These add additional evidence and further confirm that late-spring temperature controls the onset of cambial activity and the kinetics of cell formation in cold environments (Kirdyanov et al, 2003;Seo et al, 2008;Thibeault-Martel et al, 2008;Moser et al, 2010;Olano et al, 2013). However, we also observed waterrelated constraints on tracheid morphogenesis.…”
Section: Intra-ring Anatomy Reflects Climate Impact On Cell Morphogensupporting
confidence: 73%
“…Stronger and more defined associations emerged when the climatic data were aligned according to the DD temperature thresholds at high elevation (especially for CD in the first ring sectors; Figs 6 and 7), but not at lower elevations (see Cuny et al, 2015). These add additional evidence and further confirm that late-spring temperature controls the onset of cambial activity and the kinetics of cell formation in cold environments (Kirdyanov et al, 2003;Seo et al, 2008;Thibeault-Martel et al, 2008;Moser et al, 2010;Olano et al, 2013). However, we also observed waterrelated constraints on tracheid morphogenesis.…”
Section: Intra-ring Anatomy Reflects Climate Impact On Cell Morphogensupporting
confidence: 73%
“…Mediterranean summer drought stops growth in Q. ilex, resulting in bimodal secondary growth patterns (Lempereur et al 2015). A transient quiescence of growth has also been reported for Mediterranean conifers (Camarero et al 2010;Vieira et al 2014) and forbs (Olano et al 2013). Large below-and above-ground bud banks are also characteristically associated with Mediterranean vegetation (Canadell and Lopez-Soria 1998;Klimešová and Klimeš 2007) and its capacity to recover from fires but are also relevant after extreme droughts (Zeppel et al 2015).…”
Section: Quercus Ilex As a Paradigmatic Mediterranean Speciesmentioning
confidence: 79%
“…von found that annual ring widths of forbs in the Wallowa Mountains (northeastern Oregon, USA) declined linearly with age at low and intermediate altitudes, but increased for the first few years and then declined in later years at high altitudes. In addition, Olano et al (2013) showed that ring width of the alpine forb, Silene ciliate, decreased with plant age at all altitudinal zones (from 1986 to 2413m) in Mediterranean high mountains. On the contrary, Liu and Zhang (2007) found that ring widths of forbs in the Mongolia grassland indicated a linear increasing trend with age.…”
Section: Patterns Of Growth Ring Width and Life History Strategymentioning
confidence: 95%
“…Previous studies have suggested that annual growth rings are widespread among perennial forbs in the regions located at rather higher latitudes (above 40 • N), such as the central European lowlands (Dietz and Ullmann, 1997;Dietz and Fattorini, 2002), North America (Dietz and Schweingruber, 2002;Dietz and von Arx, 2005;, Mediterranean (Olano et al, 2013) and Inner Mongolia grassland (Liu and Zhang, 2007). In contrast, we detected distinguishable growth rings of many perennial forbs at the Loess Plateau located at comparatively lower latitudes (from 35 to 39 • N), and we hypothesized those perennial forbs with annual rings might widespread in the temperate seasonal zones of the Northern Hemisphere.…”
Section: Presence and Patterns Of Annual Growth Ringsmentioning
confidence: 99%
See 1 more Smart Citation